2018
DOI: 10.1155/2018/3926745
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Foveal Microvascular Abnormalities in Diabetic Retinopathy Using Optical Coherence Tomography Angiography with Projection Artifact Removal

Abstract: Purpose To analyze foveal microvascular abnormalities in different stages of diabetic retinopathy (DR) using optical coherence tomography angiography (OCTA) with projection artifact removal (PAR). Methods We analyzed 93 eyes of 59 patients with diabetes—31 with no DR (no DR), 34 with mild to moderate nonproliferative DR (mild DR), and 28 with severe nonproliferative DR to proliferative DR (severe DR)—and 31 age-matched healthy controls. Sections measuring 3 × 3 mm2 centered on the fovea were obtained using OCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
3
29
1
2
Order By: Relevance
“…However, the new SQI also takes motion artefacts and image defocus into consideration. Numerous previous studies have reported on the OCTA image quality using the SSI but more recent studies are using SQI . Direct comparison between these values for individual patient is not possible since users can no longer access the SSI values once the software is upgraded to Phase 7.0.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the new SQI also takes motion artefacts and image defocus into consideration. Numerous previous studies have reported on the OCTA image quality using the SSI but more recent studies are using SQI . Direct comparison between these values for individual patient is not possible since users can no longer access the SSI values once the software is upgraded to Phase 7.0.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold was also used in the Hwang et al study for quantification of capillary non‐perfusion in DR. A higher threshold of SSI ≥60 was used by other studies, such as Mastropasqua et al to analyse VR in patients with RVO complicated with macular oedema, and Golebiewska et al to assess OCTA features in children with type 1 DM. Conversely, in more recent studies using Optovue device, an SQI of ≥6 was used as the threshold for acceptable images . However, none of the above studies provided a scientific justification for the minimum SSI or SQI threshold chosen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of parameters in the foveal area were obtained using the built-in AngioAnalytics software (version 2017.1.0.151; Optovue, Fremont, California, USA). In the FAZ quantitative analysis, the area, perimeter, and the acircularity index (AI) were evaluated as in a previous study [18]. The AI was measured using the following equation: AI = perimeter calculated/standard circular perimeter of the equal area.…”
Section: Faz and Foveal Microcirculation Parameters Collectionmentioning
confidence: 99%